A new type of simulated partial gravity apparatus for rats based on a pully-spring system - Zhang, Shenke; Adachi, Takuya; Zhang, Shengli; Yoshida, Yukari; Takahashi, Akihisa (Frontiers in Cell and Developmental Biology, 2022)
The return to the Moon and the landing on Mars has emphasized the need for greater attention to the effects of partial gravity on human health. Here, we sought to devise a new type of simulated partial gravity apparatus that could more efficiently and accurately provide a partial gravity environment for rat hindlimbs. The new apparatus uses a pulley system and tail suspension to create the simulated partial gravity of the rat’s hind limbs by varying the weight in a balance container attached to the pulley system. An experiment was designed to verify the reliability and stability of the new apparatus. In this experiment, 25 seven-week-old male Wistar Hannover rats were randomly divided into five groups (n = 5 per group): hindlimb full weight-bearing control (1G), sham (1G), and the simulated gravity groups including Mars (3/8G), Moon (1/6G), and interplanetary space (microgravity: µG). The levels of partial gravity experienced by rat hindlimbs in the Mars and Moon groups were provided by a novel simulated partial gravity device. Changes in bone parameters [overall bone mineral density (BMD), trabecular BMD, cortical BMD, cortical bone thickness, minimum moment of area (MMA), and polar moment of area (PMA)] were evaluated using computed tomography in all rats at the proximal, middle, and distal regions of femur and tibia. Reduced gravity led to decreases in bone parameters (overall BMD, trabecular BMD, cortical BMD, MMA, and PMA) in the simulated gravity groups, mainly in distal femur and proximal tibia. The proximal tibia, MMA, and PMA findings indicated greater weakness in the µG group than in the Mars group. The sham group design also excluded the decrease in lower limb bone parameters caused by the suspension attachment of the rat’s tail. The new simulated partial gravity apparatus can provide a continuous and stable level of partial gravity. It offers a reliable and valuable model for studying the effects of extraterrestrial gravity environments on humans.